Meat Safety Inspection in Senegal: Example of the Dakar Slaughterhouse from 2014 to 2018 - fall cheikh (Meat and Muscle Biology, 2020)
Meat inspection at slaughterhouses is among the most important responsibilities given to the Directorate of Veterinary Services in Senegal. The objective of this 5-year retrospective (2014–2018) study is to give an overview of the main seizure reasons and quantities of red meat (cattle, sheep, and goats) seized in the Dakar slaughterhouse, the biggest facility in the country. Data were collected from annual reports and analyzed using Microsoft Excel, 2019. In total, red meat seizures in this slaughterhouse represented around 0.15% of the total weight of slaughters and are valued at $123,440 (United States dollars) annually. Tuberculosis, cysticercosis, and putrefaction account for 80% of the weight of cattle carcasses seized. Distomatosis due to Fasciola gigantica represented more than 50% of the total weight of cattle organs seized. The very limited contribution of meat inspection to the animal diseases surveillance system, the absence of laboratory investigations to clarify findings, the lack of identification of slaughter animals, and the noncodification of seizure-reason terminology limit the use of available data. Greater attention should be paid to the quality of data recorded at slaughterhouses and to the occurrence and burden of tuberculosis, distomatosis, and cysticercosis so that control strategies can be developed to address them in Senegal.